(untitled) (Prosiding Keislaman dan Sains, 2025)
This study aims to evaluate the effectiveness of the Discovery Learning model in improving students’ learning outcomes in Akidah Akhlak at MAN 1 Siak. Using a quasi-experimental research design with experimental and control groups, the study involved 60 students divided into two groups: one group received the Discovery Learning treatment, while the other group used conventional lecture methods. Data were collected through learning outcome tests (pretest and posttest), observations of learning activities, and questionnaires assessing students’ responses to the teaching method. The analysis results show that the Discovery Learning model significantly improved students’ learning outcomes, with the experimental group’s posttest average score increasing by 31%, compared to 16.8% in the control group. Observations also showed higher student participation in discussions and group activities in the experimental group compared to the control group. As many as 90% of students reported that the method made it easier for them to understand Akidah Akhlak material and enhanced their motivation to learn. The study concludes that Discovery Learning is effective in improving students’ learning outcomes, promoting active engagement, and enhancing critical thinking skills. Further training for teachers is needed to optimize the implementation of this model in madrasahs.